Dust deposition drives shifts in community structure and microbial network complexity of a planktonic microbiome in the Northwest Pacific Ocean - Wang, Yingxia; Zhuang, Yunyun; Wang, Shanshan; Chen, Hongju; Wang, Weimin; Zhang, Chao; Gao, Huiwang; Liu, Guangxing (Frontiers in Marine Science, 2024)
Dust deposition can supply nutrients to the upper ocean, and subsequently affect primary production and biodiversity in planktonic ecosystem, but the differential response among taxa and their interactions are not fully understood. Here, we performed 7-day onboard incubation experiment amended with different dust loadings (0, 0.2 and 2 mg L-1) in the Kuroshio-Oyashio transition region of the Northwest Pacific Ocean and characterized the community structure and microbial network of a planktonic microbiome in response to dust addition. Chlorophyll a and nutrient analysis indicated that dust-derived nitrogen promoted the growth of phytoplankton (165.8–293.6%) and phytoplankton size structure shifted towards larger cells (>3 μm). Metabarcoding sequencing, targeting prokaryotic and eukaryotic microbes, revealed the changes in community structure and co-occurrence network in response to dust addition. Dust induced a shift from dinoflagellate dominance toward diatom dominance in phytoplankton, and favored members of Cercozoa, Labyrinthulomycetes and Saprospirae, which showed positive correlation with diatom. Temporal response patterns among taxa were categorized into five clusters, and collectively pointed to a more sensitive microeukaryotic community than prokaryotic one in response to dust. The community turnover during the incubation was dominated by moderate taxa with 55.71-62.26% moderate OTUs transitioning to abundant or rare taxa, and dust addition stimulated the transitions of rare taxa. Moreover, biotic factors shaped planktonic microbiome more than abiotic factors, particularly the cross-domain interaction significantly affected microeukaryotic community. Notably, dust addition enhanced the co-occurrence network complexity, with the number of keystone taxa increased, suggesting more interspecies interactions were induced by dust. With integrated analysis, our findings highlight the differential sensitivity of planktonic microbiome to dust deposition and the effects could pass on other organisms through interspecies interaction.